The Relationship Between Modern Lifestyles and Infertility in Adult Women - Inaiyah Pratiwi M. Nur (Journal of Public Health Indonesian, 2025)
Infertility among adult women has increased significantly in parallel with modern lifestyle changes characterized by chronic stress, unhealthy dietary patterns, sedentary behavior, circadian disruption, exposure to endocrine disrupting chemicals, and elevated air pollution levels. This article examines the relationship between modern lifestyle factors and female infertility through a Systematic Literature Review conducted in accordance with PRISMA guidelines. From 538  initial records, 43 studies met inclusion criteria and were thematically synthesized. Findings indicate that chronic stress disrupts the hypothalamic pituitary ovarian axis, high sugar and high fat diets impair ovulation, sedentary behavior increases oxidative stress, and circadian misalignment from shift work reduces melatonin and contributes to menstrual irregularities. Exposure to chemicals such as BPA and phthalates lowers ovarian reserve, while air pollution elevates risks of infertility and miscarriage. The study highlights the need for integrative public health strategies, including lifestyle education, environmental regulation, workplace health reforms, and expanded access to fertility care